If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 7x + x = 43 Combine like terms: 7x + x = 8x 3 + 8x = 43 Solving 3 + 8x = 43 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 8x = 43 + -3 Combine like terms: 3 + -3 = 0 0 + 8x = 43 + -3 8x = 43 + -3 Combine like terms: 43 + -3 = 40 8x = 40 Divide each side by '8'. x = 5 Simplifying x = 5
| 3+(-6x)=43 | | x/x+12=3/5 | | 3(4+2y)+3y=22 | | 16=4(z+1) | | 7y-5y=10 | | x^2-6x+2+-3x^2+5x+7= | | 16x-1=15x-100 | | 10=4+2y | | x=34-8/7 | | 2+-7-5t=11 | | (x^2-6x+2)+(-3x^2+5x+7)= | | 3x+6+4x=34 | | 7.34=.3x-x | | 35+-2y+x+2y=125 | | y-1/3=2/3 | | 8x+2y+26=3y | | x-7.34=.3x | | (5/6)t+4=2-(1/6)t | | ifz^4=16factorisez^4-16 | | 3x+5=-2-10 | | 2m-5n=200 | | 4x=-51 | | -5=x-1 | | x/3=4+x | | 10(5p-1)=7(7p-3) | | 90+x+2y=125 | | -(a-9)=3(a+5)+2 | | 3(7+3n)=6(6+n) | | 4x+36=21x-15 | | (2)(0)-2= | | 18x-45=-12 | | 4x+36=21-15 |